The Development of a Parenteral Pharmaceutical Formulation of a New Class of Compounds of Nitrosourea - Ludmila Nikolaeva; Natalia Oborotova; Natalia Bunyatyan; Xi Zhang; Ekaterina Sanarova; Anna Lantsova; Olga Orlova; Alevtina Polozkova (MDPI AG, 2016)
Despite the rapid development of medical technologies, chemotherapy treatment still occupies an important place in clinical oncology. In this regard, the current research in this area focuses on the synthesis of new highly effective antitumor substances that have minimal side effects and the development of stable pharmaceutical formulations (PF) on their basis. In order to solve this problem, the I. Ya. Postovsky Institute of Organic Synthesis of the Ural Branch of the Russian Academy of Sciences actively sought for original substances, namely, nitrosourea (NU) derivatives, one of the most promising classes of anticancer drugs. As a result of this research, a novel NU derivative was synthesized, namely ormustine, which showed high antitumor activity in preliminary preclinical trials. It is now crucial to develop an ormustine pharmaceutical formulation. Conducted technological studies showed that the most suitable solvent for the drug substance is 0.1 M hydrochloric acid, which ensures its rapid dissolution by ultrasonic treatment. A significant reduction in the concentration of the active ingredient during the storage of the solution required the development of a technique of its lyophilization and the selection of a shaper such as a Kollidon 17 PF. Upon completion of the development of a pharmaceutical formulation of ormustine, its stability after lyophilization was demonstrated, and a sufficient amount of the drug has been acquired for preclinical research.